Optimizing the Direction and Order of the Motion Unveiled the Ability of Conventional Monolayers of Human Induced Pluripotent Stem Cell-Derived Cardiomyocytes to Show Frequency-Dependent Enhancement of Contraction and Relaxation Motion - Izumi-Nakaseko, Hiroko; Chiba, Koki; Hagiwara-Nagasawa, Mihoko; Satsuka, Ayano; Goto, Ai; Nunoi, Yoshio; Kambayashi, Ryuichi; Matsumoto, Akio; Takei, Yoshinori; Kanda, Yasunari; Naito, Atsuhiko T.; Sugiyama, Atsushi (Frontiers in Cell and Developmental Biology, 2020)
Contractility of the human heart increases as its beating rate is elevated, so-called positive force-frequency relationship; however, human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) have been reported to exert a negative force-frequency relationship. We tested the hypothesis that the regulation of motion directions by electrical pacing and/or oxygen supply may improve the electro-mechanical properties of hiPSC-CMs monolayers. To better evaluate the spatial and temporal relationship between electrical excitation and contractile motion, we simultaneously observed the field potential and motion vector of hiPSC-CMs sheets. Under spontaneous contraction, although an electrical excitation originating from a region propagated unidirectionally over the cell sheet, contraction wave started from multiple sites, and relaxation wave was initiated from a geometric center of hiPSC-CMs sheet. During electrical pacing, contraction and relaxation waves were propagated from the stimulated site. Interestingly, the maximum contraction speed was more increased when the hiPSC-CMs sheet was stimulated at an area relaxation initiated under spontaneous condition. Furthermore, motion vector analysis demonstrated that “positive contraction velocity-frequency relationship” in contraction and “frequency-dependent enhancement of relaxation” were produced in the cell sheet by optimizing the direction and order of the contractile motion with pacing at the relaxation-initiating area. A close analysis of motion vectors along with field potential recording demonstrated that relaxation process consists of fast and slow phases, and suggest that intracellular Ca2+ dynamics may be closely related to functions of Ca2+-ATPase pump and Na+-Ca2+ exchangers. Namely, the slow relaxation phase occurred after the second peak of field potential, suggesting that the slow phase may be associated with extrusion of Ca2+ by Na+-Ca2+ exchangers during repolarization. Increase of oxygen concentration from 20 to 95% as well as β-adrenergic stimulation with isoproterenol accelerated the fast relaxation, suggesting that it could depend on Ca2+ uptake via Ca2+-ATPase during the depolarization phase. The ratio of maximum contraction speed to field potential duration was increased by the β-adrenergic stimulation, indicating the elevated contraction efficiency per Ca2+-influx. Thus, these findings revealed potential ability of conventional monolayers of hiPSC-CMs, which will help apply them to translational study filling the gap between physiological as well as pharmacological studies and clinical practice.